The Impacts of Indonesia's Membership in the BRICS on the Defense Sector: Opportunities and Challenges - Iqbal, Yunizir; Perwita, Anak Agung Banyu; Rudy, Elphis (Darul Yasin Al Sys, 2025)
Indonesia's accession as a full member of the BRICS in January 2025 marks strategic progress in its autonomous and proactive foreign policy, aiming to improve its economic and geopolitical position globally. The BRICS, which consists of Brazil, Russia, India, China, South Africa, and new members Indonesia, Egypt, Ethiopia, Iran, and the United Arab Emirates, serves as a forum to strengthen economic collaboration, defence diplomacy, and global security. This study analyses the impact of Indonesia's BRICS membership on the defence sector, emphasising its economic advantages, technology transfer, and enhancement of its diplomatic position. This research uses qualitative methodologies, analyses official documents, BRICS foreign policy, and reports from the Indonesian Ministry of Defence to ensure that access to the New Development Bank (NDB) facilitates infrastructure development in the fields of transportation and energy, thereby indirectly improving the operational efficiency of the military. Bilateral collaboration with BRICS countries, including Russia and China, facilitates the transfer of advanced military technologies, including weapons systems and training, thereby enhancing Indonesia's defence capabilities. In addition, BRICS membership allows Indonesia to advocate for more inclusive reforms in global economic governance, thereby enhancing its position as a link between developing countries and major economic powers. However, challenges such as potential tensions with Western allies, the risk of foreign technology dependence, and the need to maintain a balance of non-aligned policies require careful diplomacy strategies. By taking advantage of investment, trade, and BRICS multilateral forum opportunities, Indonesia can strengthen economic sovereignty and national security while becoming a key actor in regional stability. The study concludes that BRICS membership offers multidimensional opportunities for Indonesia, but long-term success depends on the ability to maintain diplomatic balance and develop a domestic defence industry to reduce asymmetric dependencies.